2000
DOI: 10.4049/jimmunol.164.4.2207
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Superantigen Staphylococcal Exfoliative Toxin A (ETA)

Abstract: Exfoliative toxin A (ETA) is known to be a causative agent of staphylococcal scalded skin syndrome (SSSS). Although relatively little is known about exactly how the exfoliative toxins (ETs) cause SSSS, much has been discovered recently that may help elucidate the mechanism(s) by which ETA exhibits activities such as lymphocyte mitogenicity and epidermolytic activity. Here, we have shown that highly purified ETA does have T lymphocyte mitogenic activity in that wild-type ETA induced T cell proliferation whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…However, detection of the toxin in these bullae was never undertaken. Finally, Rago et al (38) further investigated the topic and reported that the mitogenic activity associated with epidermolysins was not responsible for the lesions observed in the experimental model, compared to the esterase activity. Schlievert et al identified a proteolytic activity that could be exerted on ␣-and ␤-melanoma-stimulating hormones (43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, detection of the toxin in these bullae was never undertaken. Finally, Rago et al (38) further investigated the topic and reported that the mitogenic activity associated with epidermolysins was not responsible for the lesions observed in the experimental model, compared to the esterase activity. Schlievert et al identified a proteolytic activity that could be exerted on ␣-and ␤-melanoma-stimulating hormones (43).…”
Section: Discussionmentioning
confidence: 99%
“…This would corroborate epidemiological observations and explain the purulent exudates observed in impetigo bullae or erosive manifestations. There is a lack of completely satisfying experimental animal models for epidermolysin and LukE-LukD and possibly also for the mitogenic activity of epidermolysins tested in the lymphocytes of rabbits (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vector plasmid contains TT overhangs that allow for cloning of PCR products directly without restriction digestion. Subsequently, the gene was excised from this vector with EcoRI, using restriction sites on either side of the insertion site in the vector, and ligated with EcoRI-digested plasmid vector pCE104 (44). The resultant plasmid was transformed into Escherichia coli XL-1 Blue (Stratagene, La Jolla, Calif.), and a DNA insert with a restriction fragment of the proper length was verified by plasmid purification with the Qiagen Spin Miniprep kit (Qiagen, Valencia, Calif.), digestion with EcoRI, and separation in 1% agarose gels.…”
Section: Methodsmentioning
confidence: 99%
“…3 These toxins induce proteolysis by trypsin like serine proteases. 4 ETA exhibits superantigen activities.…”
Section: Sirmentioning
confidence: 97%